Bacteremia due to Staphylococcus cohnii ssp. urealyticus caused by infected pressure ulcer: case report and review of the literature - Soldera, Jonathan (2013)
CONTEXT: Coagulase-negative staphylococci are common colonizers of the human skin and have become increasingly recognized as agents of clinically significant nosocomial infections. CASE REPORT: The case of a 79-year-old male patient with multi-infarct dementia who presented systemic inflammatory response syndrome is reported. This was attributed to bacteremia due to Staphylococcus cohnii ssp. urealyticus, which was grown on blood cultures originating from an infected pressure ulcer. The few cases of Staphylococcus cohnii infection reported in the literature consist of bacteremia relating to catheters, surgical prostheses, acute cholecystitis, brain abscess, endocarditis, pneumonia, urinary tract infection and septic arthritis, generally presenting a multiresistant profile, with nearly 90% resistance to methicillin. CONCLUSIONS: The reported case is, to our knowledge, the first case of true bacteremia due to Staphylococcus cohnii subsp. urealyticus caused by an infected pressure ulcer. It shows that this species may be underdiagnosed and should be considered in the differential diagnosis for communityacquired skin infections.